(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This paper aims to study characteristics of rhetorical questions in the Uzbek language. The author mostly focuses on the usage of rhetorical questions in Uzbek literary texts. Most common examples in Uzbek prose and poetic works are analyzed